Thermal and magnetic properties of chitosan-iron oxide nanoparticles - Soares, Paula I.P.; Machado, Diana; Laia, César; Pereira, Laura C.J.; Coutinho, Joana T.; Ferreira, Isabel M.M.; Novo, Carlos M.M.; Borges, João Paulo (Carbohydrate polymers, 2016)
•Chitosan is widely used for biomedical applications.•Chitosan-iron oxide nanoparticles are suitable for magnetic hyperthermia.•Chitosan coating does not affect the properties of iron oxide nanoparticles.•Chitosan-iron oxide nanoparticles have a nanometric hydrodynamic diameter. Chitosan is a biopolymer widely used for biomedical applications such as drug delivery systems, wound healing, and tissue engineering. Chitosan can be used as coating for other types of materials such as iron oxide nanoparticles, improving its biocompatibility while extending its range of applications. In this work iron oxide nanoparticles (Fe3O4 NPs) produced by chemical precipitation and thermal decomposition and coated with chitosan with different molecular weights were studied. Basic characterization on bare and chitosan-Fe3O4 NPs was performed demonstrating that chitosan does not affect the crystallinity, chemical composition, and superparamagnetic properties of the Fe3O4 NPs, and also the incorporation of Fe3O4 NPs into chitosan nanoparticles increases the later hydrodynamic diameter without compromising its physical and chemical properties. The nano-composite was tested for magnetic hyperthermia by applying an alternating current magnetic field to the samples demonstrating that the heating ability of the Fe3O4 NPs was not significantly affected by chitosan.